THE EFFECT OF INTELLECTUAL CAPITAL, ACCOUNTING CONSERVATISM, INVESTMENT OPPORTUNITY SET (IOS), AND FIRM SIZE ON EARNINGS QUALITY - Anindita, Rizka; Kusbandiyah, Ani; Fakhruddin, Iwan; Mudjiyanti, Rina (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This study aims to examine the effect of intellectual capital, accounting conservatism, investment opportunity set (IOS), and firm size on earning quality. This study employed a quantitative approach and utilized secondary data. The population and sample for this research were companies in the basic materials sector listed on the IDX period 2019-2022. Purposive sampling was the technique used for sampling. The study’s population consisted of 28 companies in the basic materials sector, with a sample size of 90. The results showed that intellectual capital, investment opportunity set (IOS), and firm size no effect on earning quality and accounting conservatism had a positive effect on earning quality. The findings of the study indicate that intellectual capital, investment opportunity set (IOS), and firm size do not significantly influence the quality of earnings. In contrast, the research reveals a positive association between accounting conservatism and earning quality. This implies that factors such as the intellectual assets of a company, its investment opportunities, and its size do not play a substantive role in determining the quality of earnings. Conversely, the conservative approach in accounting practices is shown to contribute positively to the overall quality of reported earnings in the examined context.